PENGARUH MORALITAS APARAT DAN ASIMETRI INFORMASI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (Studi Pada Pemerintahan Kota Malang) - Nur Hizbiyatul Jannah; Nur Diana; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
AbstractThis study aims to determine the effect of individual morality andinformation asymmetry on the tendency of fraud accounting at the Organization ofthe Regional City of Malang. This type of research is quantitative research.Criteria of respondents used in this study are employees who work on thefinancial sector at the Organization of Regional Devices. The sample used was 50respondents. The number of population in this research is 19 Department which ishead of finance department and finance officer at Organization of Local Area ofMalang City. The sampling technique used is purposive sampling, with thenumber of respondents is 50 people. The results of this study indicate that (1)individual morality has a significant negative effect on the fraud of accounting (2)information asymmetry has a significant positive effect on accounting fraudtendencies, (3) individual morality and information asymmetry have a significanteffect on trends fraud (fraud) accounting.Keywords: apparatus morality, information asymmetry and fraudulent accountingtendencies.